2016
DOI: 10.2174/1745017901612010132
|View full text |Cite
|
Sign up to set email alerts
|

Working and Environmental Factors on Job Burnout: A Cross-sectional Study Among Nurses

Abstract: Background:Burnout is a problem that impacts on the staff management costs and on the patient care quality.Objective:This work aimed to investigate some psychosocial factors related to burnout. Specifically, we explored the sample characteristics for moderate/high emotional exhaustion, cynicism and professional inefficacy, as well as the relationship between both working and environmental variables and burnout.Method:A cross-sectional study involving 307 nurses from one Italian hospital was carried out. A self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 33 publications
4
43
1
7
Order By: Relevance
“…Las demandas emocionales en enfermería surgen en la interacción con el sujeto de cuidado de diversas maneras porque la enfermera no solo se centra en los problemas de salud de su paciente, sino que también puede ser afectada por aspectos de índole emocional, familiar, social o laboral (13,44,80,81). Estas demandas aparecen cuando en su labor el profesional en enfermería se enfrenta a situaciones complejas en la atención de pacientes, principalmente en servicios de salud mental, urgencias y cuidados intensivos, en los cuales interactúa con individuos críticamente enfermos, conflictivos, moribundos o en condiciones de especial complejidad (23,44,71,(82)(83)(84).…”
Section: Doble Presenciaunclassified
“…Las demandas emocionales en enfermería surgen en la interacción con el sujeto de cuidado de diversas maneras porque la enfermera no solo se centra en los problemas de salud de su paciente, sino que también puede ser afectada por aspectos de índole emocional, familiar, social o laboral (13,44,80,81). Estas demandas aparecen cuando en su labor el profesional en enfermería se enfrenta a situaciones complejas en la atención de pacientes, principalmente en servicios de salud mental, urgencias y cuidados intensivos, en los cuales interactúa con individuos críticamente enfermos, conflictivos, moribundos o en condiciones de especial complejidad (23,44,71,(82)(83)(84).…”
Section: Doble Presenciaunclassified
“…A cross-sectional study in Spain showed a negative relationship between emotional exhaustion and each of sta ng and resources adequacy and nurse manager ability, leadership, and support of nurses (21). Furthermore, teamwork climate manifested in good working relationships and communication between nurses was signi cantly associated with low emotional exhaustion among nurses working in Brazilian (46) and Italian hospitals (22). Our ndings complement these results and further suggest that several aspects of the working environment are related to musculoskeletal and mental/emotional health among nurses with more direct relationships between certain physical-related demands and musculoskeletal disease whereas associations with mental health problems and mental health exhaustion is diffuse and widespread across 7 of the 10 investigated workrelated factors.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to the nature of the nursing tasks -which are largely stress-inducing and put nurses in routine exposure to grief and suffering of others - (6,19,21,22), data show that work environment factors in healthcare institutions are associated with nurses' physical (9,23,24) and emotional (21,22,(25)(26)(27) health. Several aspects of the work environment in hospitals have been suggested to in uence nurses' health, including workload demands, nurse manager ability, leadership and support of nurses, sta ng and resource adequacy, and workplace teamwork climate (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Persons who aspire to perfectionism have a particular tendency to this syndrome, as those with the unreal expectations and estimations connected with themselves and their own job. Some conflicts connected with the professional roles result in emotional exhaustion and ambivalent attitude to their job, low protection of co-workers and reduce working potential and create a sense of low accomplishment and low confidence [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%